Dental Status and Associated Factors in a Dentate Adult Population in Bulgaria: A Cross-Sectional Survey - Nikola D. Damyanov; Dick J. Witter; Ewald M. Bronkhorst; Nico H. J. Creugers (International Journal of Dentistry)
This study aimed to determine variations in the dental status of a dentate adult population in terms of “decayed,” “missing,” and “filled” teeth in relation to several sociodemographic and behavioral factors. Quota sampling was used to draw 2531 subjects aged 20 years and over. Data were collected by means of a questionnaire and an oral examination. Multiple logistic regression analyses were performed to observe associations between “decayed,” “missing,” and “filled” teeth and the factors of interest. The mean numbers of “decayed,” “missing,” and “filled” teeth were 2.2, 6.7, and 4.9, respectively. Molar teeth were significantly more often “missing” than premolar and anterior teeth. Age, gender, education, and tooth brushing revealed most noticeable associations. Increasing age was associated with a lower chance of having “decayed” and “filled” teeth, but with a higher chance of having “missing” teeth. Females were more likely to have “missing” and “filled” teeth. Higher education was associated with a lower chance of having “missing” teeth. More frequent tooth brushing was associated with a lower chance of having “decayed” and “missing” teeth, but with a higher chance of having “filled” teeth. These risk indicators should be considered in prevention program planning if reduction of tooth loss is to be achieved.